2005
DOI: 10.1149/1.1960173
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Degradation of N-Channel Poly-Si TFT under AC Stress

Abstract: The degradation of n-channel poly-silicon thin film transistor ͑poly-Si TFT͒ has been investigated under dynamic voltage stress. The ON-current of TFT is 0.03 times the initial value after 1000 s stress. However, both the sub-threshold swing and threshold voltage almost kept well during the ac stress. The current crowding effect was rapidly increased with the increasing of stress duration. The creation of effective trap density in tail-states of poly-Si film is responsible for the electrical degradation of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Similarly, the device degradation solely depends on the pulse transition of V g , rather than high or low V g biases. It was observed that shortening t f enhances the degradation while t r has little impact on the degradation [5][6][7][8][9]. A dynamic HC mechanism associated with V g switching controls the degradation [5][6][7][8][9]].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the device degradation solely depends on the pulse transition of V g , rather than high or low V g biases. It was observed that shortening t f enhances the degradation while t r has little impact on the degradation [5][6][7][8][9]. A dynamic HC mechanism associated with V g switching controls the degradation [5][6][7][8][9]].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that shortening t f enhances the degradation while t r has little impact on the degradation [5][6][7][8][9]. A dynamic HC mechanism associated with V g switching controls the degradation [5][6][7][8][9]]. An earlier model proposes that as V g pulse swings from ON state to OFF state (determined by device V th ), some remaining channel electrons that have no enough time to return S/D will be exposed to a high coupling electric field and to be accelerated to HCs [7][8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations